P132 Quality of Guidelines Developed by the World Health Organization: Preliminary Results. (15th August 2013) - Burda, B; Chambers, A
Abstract : Background: The World Health Organization (WHO) annually publishes hundreds of guidelines. Its guideline development process, however, is often criticised even after the implementation of a Guideline Review Committee (GRC) that ensure guidelines are developed using the highest methodological quality, transparent and evidence-based processes. Objectives: To quality rate a cohort of GRC-approved WHO guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE) II tool. Methods: We searched the WHO website for GRC-approved guidelines published between 2008 and November 2012. Two individuals independently appraised the guidelines using AGREE II. Scores were standardised across six domains and overall quality was determined through consensus. Results: Eighty guidelines fulfilled inclusion criteria and were appraised. Twenty-seven guidelines were recommended, 47 were recommended with modifications, and six were not recommended. Two domains of AGREE scored highly across all guidelines: scope and purpose and clarity of presentation. The rigour of development and applicability domains were variable across guidelines. The lowest scoring domains were stakeholder involvement and editorial independence. Discussion: WHO guidelines still need improvement in the following areas: stakeholder engagement, use of systematically reviewed evidence, defining the funder's role, consideration of barriers and resources (including costs) when implementing recommendations, and providing monitoring criteria. Most issues may be resolved through increased transparency and better reporting of the recommendation development process by more closely following the standards set forth in the WHO guideline development handbook. Implications for Guideline Developers/Users: Guideline developers need to ensure systematic guideline development processes are followed and adequately reported in each guideline.